Secondary Treatment Facilitating the Mechanical Recycling of Film-Coated Waste Automobile Bumpers - Tetsuo Takayama; Toshiyuki Niiyama; Tadao Tanabe; Jeongsoo Yu (Recycling)
Concerns have been raised regarding the mechanical recycling rates of automotive parts, which appear to be low in comparison to those of other sectors. Addressing this issue demands the promotion of the mechanical recycling of waste automobile bumpers. This study investigates primer treatment effects on the mechanical properties of injection-molded waste bumpers. The primer treatment effects vary depending on the bumper coating. The flexural strength of coated bumpers is greater: 27.6 MPa vs. 29.2 MPa. The flexural modulus is also greater: 1667 MPa vs. 1761 MPa. By contrast, the notched Charpy impact strength is less: 25.4 kJ/m2 vs. 23.4 kJ/m2. The flexural strength and flexural modulus of the bumpers lacking a coating are also lower, respectively, at 25.0 MPa vs. 22.9 MPa and 1523 MPa vs. 1314 MPa. However, the notched Charpy impact strength is greater: 40.0 kJ/m2 vs. 73.6 kJ/m2. These findings suggest that primer treatment can control the mechanical properties of injection-molded parts produced from waste automobile bumpers, which is an important achievement for promoting the mechanical recycling of waste automobile bumpers.